Gibbs distribution for statistical analysis of graphical data with a sample application to fcMRI brain images. (25th November 2015) - La Rosa, Patricio S.; Brooks, Terrence L.; Deych, Elena; Shands, Berkley; Prior, Fred; Larson‐Prior, Linda J.; Shannon, William D.
Abstract : This paper develops object‐oriented data analysis (OODA) statistical methods that are novel and complementary to existing methods of analysis of human brain scan connectomes, defined as graphs representing brain anatomical or functional connectivity. OODA is an emerging field where classical statistical approaches (e.g., hypothesis testing, regression, estimation, and confidence intervals) are applied to data objects such as graphs or functions. By analyzing data objects directly we avoid loss of information that occurs when data objects are transformed into numerical summary statistics. By providing statistical tools that analyze sets of connectomes without loss of information, new insights into neurology and medicine may be achieved. In this paper we derive the formula for statistical model fitting, regression, and mixture models; test their performance in simulation experiments; and apply them to connectomes from fMRI brain scans collected during a serial reaction time task study. Software for fitting graphical object‐oriented data analysis is provided. Copyright © 2015 John Wiley & Sons, Ltd.